Pemberdayaan MP-ASI Lokal sebagai Upaya Pencegahan Stunting pada Masyarakat Pesisir di Gampong Pusong Lama Kecamatan Banda Sakti Kota Lhokseumawe - Ardilla, Arista; Harkensia, Linur Steffi; Khana, Fitri Hijri; Fauziah, Fauziah; Zulkarnaini, Zulkarnaini (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Bacground Stunting remains a chronic nutritional problem in Indonesia. One approach to preventing stunting is by strengthening the utilization of local wisdom in food resources. In Lhokseumawe City, locally available seafood, which is a high-protein food source, is abundant. However, many members of the community are unaware of the nutritional benefits of these local ingredients. Purpose of this community service activity is to enhance the empowerment of locally sourced complementary feeding as an effort to prevent stunting in coastal communities in Gampong Pusong Lama, Banda Sakti District, Lhokseumawe City. The implementation method began with planning, followed by the lectures, animated video screenings, distribution of booklets and posters, and demonstrations on preparing complementary feeding using local food ingredients. This health education activity was conducted over a single day. Monitoring and evaluation were carried out by measuring participants' knowledge seven days after the education session. Results of this community service showed a 50% increase in participants' knowledge after being provided with health education through booklets, animated videos, posters, lectures, and demonstrations. Conclusion This activity needs to be conducted continuously to help prevent the rise of stunting in young children by utilizing local food as a primary, affordable, and accessible source of nutrition.